PERBANDINGAN KINERJA KEUANGAN PT. TELKOM INDONESIA (Persero) Tbk. DAN PT. XL AXIATA Tbk. PERIODE TAHUN 2020-2021 - Hartono, M. Edhie; Hermuningsih, Sri (Jurnal Ilmiah Manajemen, Bisnis dan Kewirausahaan, 2023)
The research conducted aims to analyze the comparison of financial performance at PT. Telkom Indonesia Tbk. With PT. XL Axiata in 2020 and 2021. In this study the method used is quantitative with manual calculations. The results of the study show that there are several financial performances that show differences between PT. Telkom Indonesia (Persero) Tbk. And PT. XL Axiata Tbk. Asset Management Ratio (Asset Ratio) PT. Telkom Indonesia (Persero) Tbk. Shows a fairly good ratio, this is due to the increase from year to year and the company is able to maximize its assets and is different from PT. XL Axiata Tbk. Which shows a decline during 2020 and 2021 so that the company has not been able to make maximum use of its assets.